2021
DOI: 10.1101/2021.08.17.456671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection and phenotypic characterization of carbapenem non susceptible gram-negative bacilli isolated from clinical specimens

Abstract: Background Multi-drug resistant, extremely drug-resistant, pan-drug resistant, carbapenem-resistant, and carbapenemase-producing gram-negative bacteria are becoming more common in health care settings and are posing a growing threat to public health. Objective The study was aimed to determine the magnitude of multi-drug resistant, extremely drug-resistant, carbapenem non-susceptible, and carbapenemase-producing gram-negative bacilli at Ethiopian Public Health Institute. Materials and methods Prospective c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
6
2
2
Order By: Relevance
“…The most concerning finding in this study was that E. coli, K. pneumoniae, A. baumannii, and P. aeruginosa were almost all of the pathogens classified as serious life-threatening pathogens (ESKAPE) by WHO, 2019. Our result concurs with the reports of many local studies (Beyene et al, 2019;Abdeta et al, 2021) and global studies (Agyepong et al, 2018;Makanjuola et al, 2018). Furthermore, cases of infections caused by infrequently isolated bacteria, including Burkholderia cepacia, Cupriavidus pauculus, Stenotrophomonas matophilia, Methylobacterium.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The most concerning finding in this study was that E. coli, K. pneumoniae, A. baumannii, and P. aeruginosa were almost all of the pathogens classified as serious life-threatening pathogens (ESKAPE) by WHO, 2019. Our result concurs with the reports of many local studies (Beyene et al, 2019;Abdeta et al, 2021) and global studies (Agyepong et al, 2018;Makanjuola et al, 2018). Furthermore, cases of infections caused by infrequently isolated bacteria, including Burkholderia cepacia, Cupriavidus pauculus, Stenotrophomonas matophilia, Methylobacterium.…”
Section: Discussionsupporting
confidence: 94%
“…The poor regulatory system for antimicrobial agents over the counter and the supply of substandard antimicrobials are some of the other factors that facilitate the spread of drug-resistant bacteria (Osei-Safo et al, 2016;Sharma et al, 2017). Studies conducted in Africa, including Ethiopia, have demonstrated a mounting prevalence of Gramnegative bacteria resistant to commonly prescribed antibiotics (Kariuki and Dougan, 2014;Beyene et al, 2019;Tafese et al, 2020;Abdeta et al, 2021;Moges et al, 2021). Poor drug regulatory systems, a lack of established antibiotic stewardship, and a lack of laboratory testing capacities in Ethiopia dictate continuous surveillance studies on the level of drug resistance, the phenotypic profile of ESBLase, and carbapenemase producing GNB in different health settings.…”
Section: Introductionmentioning
confidence: 99%
“…Those who frequently consumed alcohol, such as beer and tela, and were infected with K. pneumoniae had a greater likelihood of developing severe symptoms, accounting for 42.9% of the patients. These ndings are consistent with many related studies [1,3,6,16,17,34,36,39].The maternal sepsis incidence and treatment of K. pneumoniae vary by region. This could be due to different factors such as sample type, geographic location, patient demographics, immune status, and co-infections, can affect the magnitude and strain type of this bacterium, which is consistent with our ndings in ve tertiary hospitals [10,15,24,35,37].…”
Section: Sociodemographic Characteristics and Epidemiology Of K Pneum...supporting
confidence: 92%
“…Without addressing the rapid spread of CRKP strains, there may not be alternative treatments available in the near future. These ndings are consistent with many studies carried out in other counties [34][35][36][37]. On the other hand, this bacterium is one of the most commonly acquired both nosocomial and community infections and is highly spreading and developed antimicrobial resistance in the worldwide [10-14, 23, 24].…”
Section: Antimicrobial Resistance Pro Le Of K Pneumoniaesupporting
confidence: 89%
See 1 more Smart Citation